PENGARUH PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KOMITMEN ORGANISASI YANG BERDAMPAK PADA KINERJA PEGAWAI NON MEDIS DI RUMAH SAKIT MITRA SEHAT SITUBONDO - Anggraini, Indri Dwi; Soeliha, Siti; Tulhusnah, Lusiana (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
ABSTRACT Mitra Sehat Situbondo Hospital is a private public hospital and is one of the type D hospitals located in the Situbondo Regency area. As a community service, hospital employees certainly need training, as well as a comfortable work environment and there must be organizational commitment. The purpose of this study was to analyze and examine the effect of training and work environment on organizational commitment that has an impact on the performance of non-medical employees at Mitra Sehat Hospital, Situbondo. The sampling technique used was the saturated sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation - Partial Least Square (PLS-SEM) model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicating that the Effect of Training has no significant effect on Organizational Commitment, Work Environment has a significant effect on Organizational Commitment, the influence of training has a significant effect on employee performance, the work environment has a significant effect on employee performance, organizational commitment has a significant effect on employee performance. The results of the indirect effect hypothesis test show that the variable Effect of Training on Employee Performance through Organizational Commitment has a positive but not significant effect, Organizational Commitment on Employee Performance through Organizational Commitment has a significant positive effect.